Systems-Level Mapping of Cancer Testis Antigen 1b/a to Sarcoma Pathways Identifies Activated Ran Binding-2 E3 SUMO-Protein Ligase and Transducin-Like Enhancer Protein 1 - Papanikolaou, Nikolaos A.; Hytiroglou, Prodromos; Pantelidou, Pavlina; Papavassiliou, Athanasios G.; Old, Lloyd L. (Frontiers in Genetics, 2022)
Here we describe the reconstruction of a sarcoma cancer testis gene 1b/a (catg1b/a) network and its use to identify genes and proteins expressed in advanced grade tumors. Background: CTAG1B/A is an ortholog of the yeast/Drosophila transcription factor Pcc1p, and a member of the KEOPS transcription complex. It has been implicated in telomere maintenance and transcriptional regulation through association with chromatin remodeling factors and is only expressed during adult testis germ cell differentiation. CTAG1B/A is re-activated in grade three synovial and myxoid liposarcomas but not in benign differentiated liposarcomas. Methods: We mapped CTAG1B/A to sarcoma transcription pathways with gene set expression analysis (GSEA) and network reconstruction. Using independent samples, we immunohistochemically identified expression of two network neighbors, RANBP2, and TLE1, thus validating our approach. Conclusion: This work demonstrates that mapping unknown genes to functional pathways by network re-construction is a powerful tool that can be used to identify candidate oncoproteins.